Halal Management And Corporate Social Responsibility: A Convergent Model For Sustainable Business - Ushwa Dwi Masrurah Arifin Bando; Hasnidar; Rostina (Journal of Studies in Academic, Humanities, Research, and Innovation, 2025)
This study aims to construct a convergent model integrating halal management and corporate social responsibility (CSR) as a foundation for sustainable business practices guided by Islamic values. Using a qualitative conceptual approach, the research employs descriptive analysis through an extensive literature review of contemporary halal management frameworks, CSR theories, and sustainability models. The analysis identifies key principles within halal management—such as honesty (shiddiq), trustworthiness (amanah), consistency (istiqamah), intelligence (fathanah), and social responsibility (tabligh)—and examines their alignment with the economic, social, and environmental dimensions of CSR. The findings reveal that halal management and CSR share strong complementary characteristics, particularly in promoting ethical conduct, transparency, and balanced stakeholder engagement. These shared values form the basis of a convergent model that extends CSR beyond philanthropy by embedding spiritual accountability and Islamic ethical principles into business operations. The proposed model positions CSR not merely as voluntary corporate action but as an act of worship (ibadah) rooted in the pursuit of collective welfare (maslahah). It emphasizes that sustainable business must balance profit generation with moral integrity, environmental stewardship, and social justice. Furthermore, the integrated model contributes to the field of Islamic management by offering a broader framework for managerial decision-making within Muslim-majority contexts, particularly Indonesia. The study highlights the importance of aligning modern sustainability practices with Islamic ethical foundations to strengthen corporate legitimacy, stakeholder trust, and long-term competitiveness. Overall, the convergence of halal management and CSR presents a holistic and value-driven approach to sustainable business.